SemBioNLQA: A semantic biomedical question answering system for retrieving exact and ideal answers to natural language questions - Sarrouti, Mourad; Ouatik El Alaoui, Said (Artificial intelligence in medicine, 2020)
[Display omitted] •A new semantic biomedical question answering system named SemBioNLQA for retrieving exact and ideal answers to natural language questions is presented.•SemBioNLQA, a fully automatic system, integrates NLP methods in question classification, document retrieval, passage retrieval and answer extraction modules.•It is able to accept a variety of natural language questions and to generate appropriate natural language answers.•Experimental evaluations performed on biomedical questions provided by the BioASQ challenge show that SemBioNLQA achieves good performances compared with the current state-of-the-art systems.•The SemBioNLQA source code is available at https://github.com/sarrouti/sembionlqa. Question answering (QA), the identification of short accurate answers to users questions written in natural language expressions, is a longstanding issue widely studied over the last decades in the open-domain. However, it still remains a real challenge in the biomedical domain as the most of the existing systems support a limited amount of question and answer types as well as still require further efforts in order to improve their performance in terms of precision for the supported questions. Here, we present a semantic biomedical QA system named SemBioNLQA which has the ability to handle the kinds of yes/no, factoid, list, and summary natural language questions. This paper describes the system architecture and an evaluation of the developed end-to-end biomedical QA system named SemBioNLQA, which consists of question classification, document retrieval, passage retrieval and answer extraction modules. It takes natural language questions as input, and outputs both short precise answers and summaries as results. The SemBioNLQA system, dealing with four types of questions, is based on (1) handcrafted lexico-syntactic patterns and a machine learning algorithm for question classification, (2) PubMed search engine and UMLS similarity for document retrieval, (3) the BM25 model, stemmed words and UMLS concepts for passage retrieval, and (4) UMLS metathesaurus, BioPortal synonyms, sentiment analysis and term frequency metric for answer extraction. Compared with the current state-of-the-art biomedical QA systems, SemBioNLQA, a fully automated system, has the potential to deal with a large amount of question and answer types. SemBioNLQA retrieves quickly users’ information needs by returning exact answers (e.g., “yes”, “no”, a biomedical entity name, etc.) and ideal answers (i.e., paragraph-sized summaries of relevant information) for yes/no, factoid and list questions, whereas it provides only the ideal answers for summary questions. Moreover, experimental evaluations performed on biomedical questions and answers provided by the BioASQ challenge especially in 2015, 2016 and 2017 (as part of our participation), show that SemBioNLQA achieves good performances compared with the most current state-of-the-art systems and allows a practical and competitive alternative to help information seekers find exact and ideal answers to their biomedical questions. The SemBioNLQA source code is publicly available at https://github.com/sarrouti/sembionlqa.